BMG power hits volume 6. - BMG Music (Malaysia). (Kuala Lumpur : BMG Music, 1998)
Contains twelve tracks by various artists.
CD 1 : Torn / Natalie Imbruglia (4:04) -- Wishing I Was There / Natalie Imbruglia (3:52) -- I Want You Back / 'N Sync (4:23) -- Tearing Up My Heart / 'N Sync (4:48) -- You Make Me Wanna / Usher (5:20) -- Nice And Slow / Usher (3:48) -- My Heart Will Go On / Kenny G (4:19) -- Loving You / Kenny G (3:19) -- You Promised, But You Lied / Ning (5:34) -- Always / Ning (4:31) -- Strong, Strong, Wind / Air Supply (4:23) -- Daybreak / Air Supply (4:28).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Popular music -- 1991-2000.; Songs, English